MODERN METHODS OF BIOFUEL PRODUCTION (Academia Science Repository, 2023)
Vegetable oils (calorific value 33-34 MJ/kg) have been used as motor fuel for a long time; considerable experience has been gained in the use of sunflower, peanut, soybean, corn, rapeseed and other oils. The most widely used is rapeseed oil, as rapeseed is the highest yielding of the oilseed crops.